Love letters from the other side. Analysis of documentary sources for the study of the relationship between Spanish and Moroccan during the during the forties - Pérez Rubio, Nerea; Marigil Asencio, Rocío; Naseiro Ramudo, Ana (Revista General de Información y Documentación, 2014)
Our goal is to shed light on documents part of Africa's collection, preserved in the Archivo General de la Administración (General Archive of the Administration). The starting point is the study and archival management of a “police monitoring file” and a series of referenced records, generated by the Delegación de Asuntos Indígenas de la Alta Comisaría de España en Marruecos (Foreign Affairs Delegation of the Spanish High Moroccan Commission). The study is of great interest since the Delegación de Asuntos Indígenas was in charge of the morality enforcement over the Spanish, Jewish and Moroccan population as well as foreigners residing in or related to the Protectorate. This work comprises both the sorting and classification of the police file, which served as our starting point, as well as its digitization in PARES and the study of the records referenced by this file. The studied documents are noteworthy for their diverse typology, including intercepted mail, which reveals deep love and friendship often broken at the convenience of a conservative morality.
Keywords: Protectorate; Morocco; Francoism; Correspondence; Censorship; Surveillance; Moral